Examining mentor teachers' perceptions using Mayring's qualitative content analysis (Training and Practice : Journal of Educational Sciences, 2022)
In my research, I investigated how mentors perceive the competencies of teacher educators in Hungary. In my study, I followed the combined paradigm based on Creswell's interpretive sequential design model. I wanted to present this research method on the one hand and the results of my research on the other.
Keywords: mentors; competencies; combined paradigm; qualitative content analysis